Epidemiological study of brucellosis and its effect on reproduction failures in dairy cattle in DKI Jakarta - Agus Sudibyo (Indonesian Center for Animal Research and Development (ICARD), 1995)
The purposes of this research were to observe prevalence, distribution and reproduction failure evidence of dairy cattle brucellosis in DKI Jakarta . To determine the group of cattle infected with Bntcella abortus, senim and milk samples were carried out . At the beginning, bulk of milk samples were collected from containers . Futhermore, the blood samples were simple randomly collected on cattle that were suspected positive brucellosis in the milk ring test . Those serum samples were tested by using rose bengal plate and complement fixation test . Questioner data in relation with on any reproductive failures, such as abortion, premature dead and born weak, were gathered from farmer within 8 consecutive month period . The result indicate that screening of brucellosis using milk ring test based on bulk milk sample was effective tools to determine the infected group of cattle . The average prevalence of brucellosis in DKI Jakarta area was 4 .5 %. Distribution of brucellosis prevalence were 8 .5% at Setiabudi, 2 .3% at Mampang Prapatan, and 2 .9% at Pasar Minggu . Brucellosis was found at least 201 cattle from 38 dairy cattle farm in DKI Jakarta . Brucellosis was caused abortion about 62 .5% dairy cattle and this value was significantly different than that of uninfected cattle (P<0.05) . Brucellosis also cause stillbirth around 9 .8% and born weakness 15 .2% . The widely distributed and high prevalence brucellosis of dairy cattle in DKI Jakarta was influenced by uncontrol of cattle movement and high abortion cases rate .